Digital Marketing Literacy as A Mediation of Online Business Readiness Influenced by Entrepreneurship Education (Study on Business Operators in Malang Raya) - Brian Wicaksono Ardiansyah; F. Danardana Muwarni; Ludi Wishnu Wardana; Farij Ibadil Maula (Journal of Applied Business, Taxation and Economics Research, 2023)
The current post-pandemic situation of COVID-19 presents challenges for business actors as well as challenges for the state to maintain the existence of the economy. There are many sectors of the domestic and global economy that are affected. The impact of the pandemic has been most felt in the micro, small and medium enterprise (MSMEs) sector. This is what makes the condition of MSMEs and micro and small entrepreneurs, especially in Malang Raya, paralyzed and decreased. If the country wants its economy to progress, it is important to increase businesspeople. Currently, one of the most popular forms of business in Indonesia is making purchases online. This research has implications for the development of the Unified Theory of Acceptance and Use of Technology (UTAUT) theory, a technology acceptance model that was developed based on the amalgamation of other existing technology acceptance models. As described above, this research has a novelty by completing the gaps of previous studies, conducting a comprehensive study of the online business readiness of MSMEs in Malang Raya with digital marketing literacy as a mediating variable. This research uses quantitative methods. The research population of business actors in Malang Raya with a sample of 260. Data analysis used SEM PLS. Based on the research results, it is stated that entrepreneurship education can increase the online business readiness of MSMEs in Malang Raya. Entrepreneurship education can increase digital marketing literacy of MSMEs in Malang Raya. Digital marketing literacy can improve online business readiness for MSME actors in Malang Raya. Entrepreneurship education can improve online business readiness through digital marketing literacy for MSMEs in Malang Raya. Online business readiness can be increased with good quality entrepreneurship education supported by good digital marketing literacy.